2018
DOI: 10.1037/pas0000518
|View full text |Cite
|
Sign up to set email alerts
|

Four- and five-factor models of the WAIS-IV in a clinical sample: Variations in indicator configuration and factor correlational structure.

Abstract: A growing body of research supports the validity of 5-factor models for interpreting the Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV). The majority of these studies have utilized the WAIS-IV normative or clinical sample, the latter of which differs in its diagnostic composition from the referrals seen at outpatient neuropsychology clinics. To address this concern, 2 related studies were conducted on a sample of 322 American military Veterans who were referred for outpatient neuropsychological ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Subsequently lower factor loadings were found for Gv/Gc, Gsm, and Gs. Comparing factor loadings of our best-fitting models to similar models fit with the United States standardization data show that highest factor loadings across higher-order and bifactor variants were found most consistently in Gc subtests for the Chilean WAIS-IV, and were more variable (ranging across Gc, Gv, Gf) in United States Models (Gignac, 2014; also see Niikesla et al, 2013 andStaffaroni et al, 2018). While few conclusive determinations about underlying construct validity differences can be made from these comparisons, the results from this study contribute another (albeit small) piece of information to the accumulating literature suggesting stronger cross-cultural differences in nonverbal tests and dispelling the myth of intelligence test universalism (Brickman, Cabo, & Manly;Cores et al, 2015;Daugherty, Puente, Fasfous, Hidalgo-Ruzzante, & Pérez-Garcia, 2017;Flores et al, 2017;Gasquoine, 1999;O'Bryant, Edwards, Johnson, Hall, Gamboa, & O'jile, 2018;Olson & Jacobson, 2014;Rivera Mindt et al, 2019;Rivera Mindt, Byrd, Saez, & Manly, 2010;Rosselli & Ardila, 2003).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Subsequently lower factor loadings were found for Gv/Gc, Gsm, and Gs. Comparing factor loadings of our best-fitting models to similar models fit with the United States standardization data show that highest factor loadings across higher-order and bifactor variants were found most consistently in Gc subtests for the Chilean WAIS-IV, and were more variable (ranging across Gc, Gv, Gf) in United States Models (Gignac, 2014; also see Niikesla et al, 2013 andStaffaroni et al, 2018). While few conclusive determinations about underlying construct validity differences can be made from these comparisons, the results from this study contribute another (albeit small) piece of information to the accumulating literature suggesting stronger cross-cultural differences in nonverbal tests and dispelling the myth of intelligence test universalism (Brickman, Cabo, & Manly;Cores et al, 2015;Daugherty, Puente, Fasfous, Hidalgo-Ruzzante, & Pérez-Garcia, 2017;Flores et al, 2017;Gasquoine, 1999;O'Bryant, Edwards, Johnson, Hall, Gamboa, & O'jile, 2018;Olson & Jacobson, 2014;Rivera Mindt et al, 2019;Rivera Mindt, Byrd, Saez, & Manly, 2010;Rosselli & Ardila, 2003).…”
Section: Discussionmentioning
confidence: 60%
“…This finding was not fully anticipated since the AR cross-loading is not only part of the final United States WAIS-IV reported model , AR cross-loading = 0.08) but also reported in several other studies in North American and European studies (e.g., , AR cross-loading = 0.22; van Aken et al, 2017, AR cross-loading = 0.32). At least one other study, however, showed a negative cross-loading of AR on Gc in a clinical population (Staffaroni et al, 2018) and it is possible other studies encountered, but did not report, a similar finding. While this may be a sample-based result (i.e., AR contributes to a verbal factor in some clinical or cultural samples but not in others), it more likely suggests that an alternate factor structure may better describe the data (e.g., an AR cross-loading on Gc is may be erroneous and inconsistent finding, or CHC model may better describe the data than a Wechsler model; Staffaroni et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations